Faktor-faktor yang Memengaruhi Penjualan dan Peramalan Volume Penjualan Pupuk Urea pada PT XYZ - Syaefuddin, Lutfiah; Setiyawan, Hery; Mariyono, Joko (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The agroindustry was an important sector in a country's economic development, serving as a key driver in the agricultural and industrial value chain. PT XYZ played a strategic role in the agroindustry sector, particularly in the production and distribution of Urea fertilizer. Based on internal data from PT XYZ, the company experienced fluctuations in Urea fertilizer sales volume over the past few years. This study aimed to analyze the influence of production volume, promotional costs, and distribution costs on the sales volume of Urea fertilizer, as well as to forecast Urea fertilizer sales at PT XYZ in 2025. The research was conducted from January 13 to February 18, 2025, using a case study method. The data sources used in the study were both primary and secondary data. The sample was determined using a non-probability sampling technique with a purposive sampling method. Data analysis was carried out using quantitative methods, including multiple linear regression analysis and trend analysis. The regression results showed that production volume and promotional costs had a significant effect on sales, while distribution costs did not have a significant effect. The sales volume forecast using the quadratic trend method indicated a positive trend, with estimated sales reaching 4,555,253 tons in 2025.